Against Reason : Schopenhauer, Beckett and the Aesthetics of Irreducibility. - Barron, Anthony (Ibidem Press, 2017)
Anthony Barron explores the relationship between the philosophy of Schopenhauer and the forms and themes of Beckett's critical and creative writings. He shows that Beckett's aesthetic preoccupations are consonant with some of Schopenhauer's seminal arguments regarding the arational basis of artistic composition and appreciation and the impotence of reason in human affairs. While Beckett's critical writings are, in places, formidably opaque, this work examines the ways in which such texts can be elucidated when their intertextual affinities with Schopenhauer's arguments are revealed. Using Schopenhauer's thought as a presiding interpretative framework, Barron demonstrates how the widespread presence of philosophical and theological ideas in Beckett's creative texts signifies less about his personal convictions than it does about his authorial aims. He thereby highlights the ways in which discursive ideas were appropriated and manipulated by Beckett for purely literary ends -- Back cover.